GOLD Mission's Observation About the Geomagnetic Storm Effects on the Nighttime Equatorial Ionization Anomaly (EIA) and Equatorial Plasma Bubbles (EPB) During a Solar Minimum Equinox - Deepak Kumar Karan; Richard W. Eastes; Robert E. Daniell; Carlos R. Martinis; William E. McClintock (Space Weather)
Abstract The nighttime ionospheric response to a geomagnetic storm that occurred on 23–29 September 2020 is investigated over the South American, Atlantic, and West African longitude sectors using NASA's Global‐scale Observations of the Limb and Disk measurements. On 27 September the solar wind conditions were favorable for prompt penetration electric fields to influence the equatorial ionosphere over extended longitudes. The equatorial ionization anomaly (EIA) crests were shifted 8°–10° poleward compared to the quiet time monthly mean across ∼65°–35°W during the main phase. Ionosonde hmF2 (peak electron density height) measurements from Fortaleza (GG: 3.9°S and 38.4°W) indicated a stronger prereversal enhancement this evening than other nights. As a result, equatorial plasma bubbles (EPB) occurred at these longitudes on this evening. This is the first simultaneous investigation of EIA morphology and EPB occurrence rate over an extended longitude range from geostationary orbit during a geomagnetic storm.